Growth and survival of rabbit-fish Siganus guttatus at different stocking densities in floating net cages - Ponce, Grande Soriano (College of Fisheries, 1986)
Five stocking densities were tested to determine the growth and survival of Siganus guttatus in fifteen units of 1 m3 floating net cages in a 1.7 ha. newly built impoundment at Binmaley, Pangasinan from August 9, 1983 to February 19, 1984 as follows : 50/cage (Treatment I) ; 100/cage (Treatment II) ; 200/cage (Treatment III) ; 300/cage (Treatment IV) and 400/cage (Treatment V). Initial stocking weight and length were 0.14 g and 2.08 cm, respectively. The highest mean weight of 36.34 g/fish obtained from Treatment I was not significantly different from the weight gain of 22.67 g/fish from Treatment II but was significantly different from the 10.83 g, 7.50 g and 5.77 g from Treatment III, IV and V respectively. The highest average survival of 70% was attained in Treatment I, followed by Treatment II (62%), Treatment III (52.2%), Treatment IV (50.1%) and Treatment V (39.5%). However, no significant difference was observed among treatments. Results indicated that the stocking densities of 200/m3, 300/m3, and 400/m3 for S. guttatus could affect its growth and survival in floating net cages. Increasing the density of the stock er cage appeared to have caused a decrease in the growth and survival of S. guttatus. Results likewise, suggested that cultured S. guttatus in floating net cages at lower stocking densities of 50 to 100 fingerlings per cage appeared promising but needs further investigations.